Co-targeting hexokinase 2-mediated Warburg effect and ULK1-dependent autophagy suppresses tumor growth of PTEN- and TP53-deficiency-driven castration-resistant prostate cancer - Wang, Lei (EBioMedicine, 2016)
Currently, no therapeutic options exist for castration-resistant prostate cancer (CRPC) patients who have developed resistance to the second generation anti-androgen receptor (AR) axis therapy. Here we report that co-deletion of Pten and p53 in murine prostate epithelium, often observed in human CRPC, leads to AR-independent CRPC and thus confers de novo resistance to second generation androgen deprivation therapy (ADT) in multiple independent yet complementary preclinical mouse models. In contrast, mechanism-driven co-targeting hexokinase 2 (HK2)-mediated Warburg effect with 2-deoxyglucose (2-DG) and ULK1-dependent autophagy with chloroquine (CQ) selectively kills cancer cells through intrinsic apoptosis to cause tumor regression in xenograft, leads to a near-complete tumor suppression and remarkably extends survival in Pten −/p53-deficiency-driven CRPC mouse model. Mechanistically, 2-DG causes AMPK phosphorylation, which in turn inhibits mTORC1-S6K1 translation signaling to preferentially block anti-apoptotic protein MCL-l synthesis to prime mitochondria-dependent apoptosis while simultaneously activates ULK1-driven autophagy for cell survival to counteract the apoptotic action of anti-Warburg effect. Accordingly, inhibition of autophagy with CQ sensitizes cancer cells to apoptosis upon 2-DG challenge. Given that 2-DG is recommended for phase II clinical trials for prostate cancer and CQ has been clinically used as an anti-malaria drug for many decades, the preclinical results from our proof-of-principle studies in vivo are imminently translatable to clinical trials to evaluate the therapeutic efficacy by the combination modality for a subset of currently incurable CRPC harboring PTEN and TP53 mutations.